High resolved snow height measurements at Neumayer Station, Antarctica, 2024 - Holger Schmithüsen; Pablo Conrat (PANGAEA, 2025)
At Neumayer-Station in Antarctica snow height is permanently monitored with a laser distance meter. The instrument measures continuously since 2013-01-01 and is located in the vicinity of the Air Chemical Observatory Neumayer. By design, the sample area of the surface is on the order of a few millimetre in diameter. Long-term trends of the measured snow height are strongly correlated with accumulation on the ice shelf at a horizontal scale of several kilometres. Short-term trends reflect dynamic changes of the surface and can be used to deduce information on surface roughness.
In: Schmithüsen, Holger (2023): High resolved snow height measurements at Neumayer Station, Antarctica (2010 et seq) [dataset publication series]. Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, PANGAEA, https://doi.org/10.1594/PANGAEA.958970